(untitled) (Research, Society and Development, 2021)
Aging is an inevitable biological process that is based on structural changes in the organism, being a progressive and singular process involving mechanisms and the inability to perform functions. The cases of falls have become a problem in public health, due to the high incidence and consequent complications for health and the care costs they generate. Physiotherapy contributes to the prevention of falls in the elderly, improving functionality, proprioception and balance, gait, muscle strength, promoting physical and mental quality of life. According to the information collected, the FisioBerg application contributes to increasing the dynamics of the assessment, gathering information and ultimately making possible a diagnosis, thus speeding up the entire process. The application is based on the Berg balance scale and the visual analog scale, which helps healthcare professionals in assessing the risk of falls and pain in the elderly. It has information and results sharing, it presents the EVA scale, it is versatile, easy and fast, having the main instruments to identify the risk of falls in the elderly, of simple operation, generating a positive intention the adherence of the health professional and academics in their use.